2012
DOI: 10.1186/1756-0500-5-148
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin prolongs the gastric emptying time in patients with diabetes mellitus and gastroparesis, but does not affect satiety or volume intake in patients with functional dyspepsia

Abstract: BackgroundOxytocin is released in response to a fatty meal. Blockage of the oxytocin receptor led to slower gastric emptying whereas stimulation resulted in less satiety in healthy volunteers. Patients with diabetes mellitus and gastroparesis lack oxytocin elevation, and dyspepsia is partly caused by reduced fundus accommodation causing early satiety and related symptoms. The aim of this study was thus to examine the effect of oxytocin on gastric emptying, satiety and volume intake in patients with gastrointes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…This finding is consistent with reports from smaller studies showing no effects of intravenous administration of oxytocin on subjective satiety in healthy individuals 77 or in patients with diabetic gastroparesis or functional dyspepsia 78 , but is in contrast to one study that reported reduced satiety in healthy individuals 79 . Furthermore, several small studies using intravenous infusions of oxytocin (20-80 mIU/min) in men and women who were healthy 79 or had functional dyspepsia 78 found that oxytocin had no effect on the volume of liquid meal intake required to induce satiety. These data highlight the importance of obtaining objective measures, such as food intake, at a test meal and/or brain imaging in this line of research.…”
Section: Eating Behavioursupporting
confidence: 91%
“…This finding is consistent with reports from smaller studies showing no effects of intravenous administration of oxytocin on subjective satiety in healthy individuals 77 or in patients with diabetic gastroparesis or functional dyspepsia 78 , but is in contrast to one study that reported reduced satiety in healthy individuals 79 . Furthermore, several small studies using intravenous infusions of oxytocin (20-80 mIU/min) in men and women who were healthy 79 or had functional dyspepsia 78 found that oxytocin had no effect on the volume of liquid meal intake required to induce satiety. These data highlight the importance of obtaining objective measures, such as food intake, at a test meal and/or brain imaging in this line of research.…”
Section: Eating Behavioursupporting
confidence: 91%
“…On the other hand, the reduced GLP-1 concentration may be a compensatory mechanism to prevent a further decrease of the emptying rate. Such a compensatory downregulating mechanism has previously been described for oxytocin, as oxytocin attenuated gastric emptying in patients with gastroparesis [22,30]. GLP-1 administration during hyperglycemia has a markedly greater impact on the gastric emptying rate compared with GLP-1 administration during euglycemia [31].…”
Section: Discussionmentioning
confidence: 79%
“…Exogenous OT, for example, has been reported in human subjects to accelerate gastric emptying of a semisolid meal (20,41) or, alternatively, to exert no effect on gastric emptying of a semisolid or solid meal (4,36). OT, moreover, slows gastric emptying in patients with diabetic gastroparesis, which is similar to its effects in mice, while lacking effects on volume of ingested nutrients, satiety, or other symptoms in patients diagnosed to have functional dyspepsia (3). Actions of exogenous OT may be complex in that OT has been reported, at least in rats, to be able to exert effects indirectly via release of cholecystokin with subsequent stimulation of cholecystokinin receptors (62,63).…”
Section: Discussionmentioning
confidence: 80%